2018
DOI: 10.1017/cts.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Social and Behavioral Research: A multisite pilot evaluation of the good clinical practice online training course

Abstract: IntroductionThe Best Practices in Social and Behavioral Research Course was developed to provide instruction on good clinical practice for social and behavioral trials. This study evaluated the new course.MethodsParticipants across 4 universities took the course (n=294) and were sent surveys following course completion and 2 months later. Outcomes included relevance, how engaging the course was, and working differently because of the course. Open-ended questions were posed to understand how work was impacted.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Indeed, Research Jams provided a unique opportunity for faculty champions to identify collaborators who have the potential to be most invested in the work before it begins. Future evaluation of Research Jams will seek to understand if and how participants' ways of working change over time using open-ended questions, such as described in Murphy et al [32], which are intended to identify a broad array of outcomes. We will map survey responses to the transtheoretical change model [33], which posits that changes in behavior progress through a series of stages, including contemplation, preparation, and action.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Research Jams provided a unique opportunity for faculty champions to identify collaborators who have the potential to be most invested in the work before it begins. Future evaluation of Research Jams will seek to understand if and how participants' ways of working change over time using open-ended questions, such as described in Murphy et al [32], which are intended to identify a broad array of outcomes. We will map survey responses to the transtheoretical change model [33], which posits that changes in behavior progress through a series of stages, including contemplation, preparation, and action.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for documentation of GCP training has been a well-established standard to ensure improved quality, safety, and compliance in clinical research. With the revision of the ICH guidelines to include E6 R2 (Step 4), including the emphasis on risk-based approaches for study development, monitoring, and quality improvement, continued calls for GCP training have been issued, especially to address the needs in Social and Behavioral clinical research and in workforce development [17][18][19]. We have described an innovative approach to GCP training using the Kaizen-Education gamification platform.…”
Section: Discussionmentioning
confidence: 99%
“…NIH-funded researchers involved in clinical trials to complete GCP training and identified various training opportunities for the workforce to meet the new requirement [ 15 ]. The original Social and Behavioral Research Best Practices course was developed in 2016 by a team at the University of Michigan (U-M) to educate clinical and translational researchers to apply GCP principles to social and behavioral research [ 16 ]. This training course, which took a median of 3.2 hours to complete, contained modules on key topics including research protocols, participant recruitment and retention, informed consent communication, confidentiality and privacy, participant safety and adverse event reporting, quality control and assurance, and research misconduct.…”
Section: Introductionmentioning
confidence: 99%
“…This training course, which took a median of 3.2 hours to complete, contained modules on key topics including research protocols, participant recruitment and retention, informed consent communication, confidentiality and privacy, participant safety and adverse event reporting, quality control and assurance, and research misconduct. A description of the development and evaluation of the original course is available elsewhere [ 16 ]. The NIH Office of Behavioral and Social Sciences Research included this course in online training resources offered to the health research workforce [ 17 ].…”
Section: Introductionmentioning
confidence: 99%